Congestion control of wireless radio access network traffic using radio over fiber - Sarkar, Md. Mahmudul Hasan; Rafique, Syed Talha; Kashem, Adnan (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.